KONSEP DESAIN ARSITEKTUR PERILAKU PADA SEKOLAH LUAR BIASA TINGKAT SMA DI SINJAI - Yusuf, Nurazizah; Rahayu, Irma; Rahmani, Ahmad Ibrahim (The Department of Architecture, Faculty of Science and Technology, Alauddin Islamic University of Makassar, 2025)
A person is considered a person with disabilities (PWD) if they experience physical limitations that affect their functions, activities, and social interactions, requiring facilities that improve accessibility. This study aims to apply the concept of behavior architecture to improve accessibility for PWD at the Special Needs School (SLB) in Sinjai by implementing accessibility features such as handrails around the site. In order to make SLB Sinjai more comfortable and accessible for deaf, speech-impaired, and visually impaired children, the design includes a lobby with stainless steel guiding paths, classrooms with ramps with a 6-degree incline covered with vinyl according to standards, and accessible toilets with stainless steel handrails at 65 cm of height.